Muzara`ah: Teori Dalam Hukum Islam Dan Aplikasinya Dalam Kerjasama Di Bidang Pertanian - Dani El Qori (MASADIR: Jurnal Hukum Islam, 2021)
Abstrak: Agriculture is the primary sector in the Indonesian economy. Massive infrastructure development has an effect on the reduction of agricultural land. A lot of land is not used by the owner because of his inability in agriculture. On the other hand, many farmers who control agriculture but do not own agricultural land. This is the background of cooperation between land owners and farmers with an agreement to share the harvest. This cooperative practice is found in many regions in Indonesia. In Islamic law this practice is identical to the muzara`ah contract. This article discusses the theory of the muzara`ah contract in the study of Islamic law and its application in cooperation in the agricultural sector. Scholars have different opinions regarding the validity of the muzara`ah contract. Hanbali, Maliki, and Hanafi madhhab scholars state that this contract is valid in Islamic law. The application of the muzara`ah contract is ideally based on togetherness and openness between the two parties. Kata Kunci : muzara`ah, cooperation, agricultural, Islamic Law